2007
DOI: 10.1073/pnas.0706618104
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Bardet–Biedl syndrome proteins causes defects in peripheral sensory innervation and function

Abstract: Reception and interpretation of environmental stimuli is critical for the survival of all organisms. Here, we show that the ablation of BBS1 and BBS4, two genes mutated in Bardet-Biedl syndrome and that encode proteins that localize near the centrioles of sensory neurons, leads to alterations of s.c. sensory innervation and trafficking of the thermosensory channel TRPV1 and the mechanosensory channel STOML3, with concomitant defects in peripheral thermosensation and mechanosensation. The thermosensory phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 37 publications
4
60
0
Order By: Relevance
“…2006; Qin et al, 2005;Tan et al, 2007). However, this might not be the case for all transmembrane proteins; for example, C. elegans ODR-10 targeting to AWB cilia was reported to require AP-1 complexes, but not IFT proteins (Dwyer et al, 2001).…”
Section: Ap-1 Ciliogenesis and Intraflagellar Transportmentioning
confidence: 94%
“…2006; Qin et al, 2005;Tan et al, 2007). However, this might not be the case for all transmembrane proteins; for example, C. elegans ODR-10 targeting to AWB cilia was reported to require AP-1 complexes, but not IFT proteins (Dwyer et al, 2001).…”
Section: Ap-1 Ciliogenesis and Intraflagellar Transportmentioning
confidence: 94%
“…Furthermore, ␤-tubulin III labeling did not reveal any alterations in microtubule structure in Bbs2 Ϫ/Ϫ or Bbs4 Ϫ/Ϫ neurons, which suggests that in some mammalian cells the function of the BBS proteins is to localize specific signaling proteins to cilia. A recent study showed altered distribution of the thermosensory channel TRPV1 and the mechanosensory channel STOML3 within the soma of peripheral neurons in BBS animals (33), suggesting that the BBS proteins may also contribute to trafficking of proteins within the cell body in some cell types.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with considerable loss of cilia because these proteins are enriched in WT OSN cilia ( intense labeling in the dendrite and cell body in Bbs8 −/− compared with Bbs8 +/− mice; in addition, SLP3 expression was heterogeneous, with cells exhibiting variable staining intensity. SLP3 mislocalization has also been observed in dorsal root ganglion neurons of other BBS models (19). We next assessed the distribution of olfactory receptor (OR) protein in individual OSNs using an antibody against ORI7, expressed by ∼0.1% of OSNs.…”
Section: Loss Of Bbs8 Reduces Olfactory Sensitivity and Causes Structmentioning
confidence: 99%